Pro-globalization via FTAs in times of COVID-19 - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2020)
This analysis attempts to offer a counter strategy to the idea of anti-globalization and de-growth that had flared up again since the COVID-19 crisis. All international forecasts expect for the year 2020 the deepest recession since the Great Depression. Countries which can afford it, run a super-Keynesian fiscal policy to fight the crisis, accompanied by an extremely expansionary monetary policy in the USA (Fed) and in the euro area (ECB). As a third policy instrument besides fiscal and monetary policy, an aggressive pro-globalization trade policy could relieve and strengthen the crisis macro policy. To demonstrate which options are available we analyze nine mega free trade agreements, some of them are already in effect, others will be enacted soon. Overall, not the big players in world trade, the EU and the USA win by a simultaneous implementation of the nine FTAs. Japan would be the winner because it participates in four combinations (overlaps) of FTAs: EU-Japan, USA-Japan, CPTPP and RCEP. The USA hardly gain from further globalization. Similarly, the EU 27 cannot profit much from further globalization.
Keywords: F13; F60; C54; C68; 330; TP_COVID; Globalization; International Trade Policy; Model Simulations; COVID-19